Textbook of cardiovascular medicine - Topol, Eric J. 1954-.; Califf, Robert M. (Philadelphia Lippincott Williams & Wilkins, 2007)
Updated throughout by renowned international authorities, Dr. Topol's best-selling text provides a comprehensive, contemporary view of every area of cardiovascular medicine, preventive cardiology; clinical cardiology; cardiovascular imaging; electrophysiology and pacing; invasive cardiology and surgical techniques; heart failure and transplantation; molecular cardiology; and vascular biology and medicine. DVD contains the full text, plus heart sounds, an image/chart/table bank, and videos of procedures, catheterization, CT/MRI, echocardiography, electrophysiology and pacing, intravascular ultrasonography, nuclear cardiology, and surgery.
Plain film examination of the chest -- Exercise electrocardiography -- Transthoracic echocardiography -- Stress echocardiography -- Doppler echocardiography -- Transesophageal echocardiography -- Imaging techniques in nuclear cardiology -- Cardiovascular magnetic resonance imaging -- Positron emission tomography -- Computed tomography of the heart -- Mechanisms of cardiac arrhythmias -- Genetics of arrhythmias -- Electrocardiography -- Ambulatory and signal-averaged electrocardiography and t-wave alternans -- Electrophysiologic testing -- Bradycardias: sinus nodal dysfunction and atrioventricular conduction disturbances -- Atrial fibrillation -- Atrial flutter -- Atrioventricular nodal-dependent tachycardias and preexcitation -- Ventricular tachycardia -- Sudden cardiac death and implantable cardioverter-defibrillators -- Sudden cardiac death in the young: the impact of inherited cardiovascular disease -- Cardiopulmonary resuscitation -- Arrhythmias in congenital heart disease -- Syncope -- Antiarrhythmic drugs -- Catheter ablation therapy for arrhythmias -- Cardiac pacemakers -- Left ventricular dyssynchrony and cardiac resynchronization therapy-- Coronary angiography -- Cardiac catheterization and hemodynamic assessment -- Percutaneous coronary intervention -- Percutaneous cardiac procedures -- Coronary artery bypass surgery -- Approaches to the patient with prior bypass surgery -- Percutaneous valve dilatations Catheter interventions in congenital heart disease -- Global pandemic of heart failure -- Pathophysiology of the heart failure clinical syndrome -- Acute heart failure -- Chronic heart failure management -- Diagnosis and medical treatment of inflammatory cardiomyopathy -- Nonischemic cardiomyopathies -- Cardiac transplantation and mechanical circulatory support -- surgical approaches for heart failure -- Prevention of heart failure -- General techniques in molecular cardiology -- Molecular genetics -- Genetic factors in atherosclerosis -- Genetic studies of myocardial and vascular disease -- Gene therapy -- Myocyte structure and function -- Signal transduction pathways of the heart -- Molecular basis of heart development -- Stem cell therapy for ischemic heart disease -- The biology of restenosis -- Therapeutic angiogenesis -- Diseases of the pulmonary vasculature -- Diseases of the aorta -- Noninvasive assessment of peripheral vascular disease -- Cerebrovascular disease -- Disease of peripheral vessels -- Renal artery disease -- Venous thromboembolism.
Includes bibliographical references and index.
System requirements for accompanying DVD-ROM: Windows or Macintosh.
Keywords: Cardiology; Cardiovascular system -- Diseases; Cardiovascular Diseases; Cardiology